Animal Magnetism: Metaphoric Cues Alter Perceptions of Romantic Partners and Relationships - Christy, Andrew G. (PLoS One, 2016)
The psychological state of love is difficult to define, and we often rely on metaphors to communicate about this state and its constituent experiences. Commonly, these metaphors liken love to a physical force—it sweeps us off our feet, causes sparks to fly, and ignites flames of passion. Even the use of “attraction” to refer to romantic interest, commonplace in both popular and scholarly discourse, implies a force propelling two objects together. The present research examined the effects of exposing participants to a physical force (magnetism) on subsequent judgments of romantic outcomes. Across two studies, participants exposed to magnets reported greater levels of satisfaction, attraction, intimacy, and commitment.